2008
DOI: 10.2341/07-54
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Solvent Evaporation Technique on the Degree of Conversion of One-Bottle Adhesive Systems

Abstract: Clinical RelevanceSince methods of solvent evaporation can change the degree of conversion for some adhesives, practitioners should be aware of the type and composition of bonding agents used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 24 publications
0
20
0
6
Order By: Relevance
“…It has been shown that the extended passive solvent volatilization that occurs when adhesive systems are left undisturbed for 60 seconds with or without posterior air-drying for 10 seconds before photoactivation may increase the DC of some commercially available adhesive systems. 12 However, little is known about the DC of contemporary adhesive systems with respect to whether an extended airactivated drying mode to volatilize the solvent should be performed before curing. Thus, this study aimed to evaluate the DC of commercially available adhesive systems when photo-activated after extended air-activated or passive methods of solvent volatilization.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the extended passive solvent volatilization that occurs when adhesive systems are left undisturbed for 60 seconds with or without posterior air-drying for 10 seconds before photoactivation may increase the DC of some commercially available adhesive systems. 12 However, little is known about the DC of contemporary adhesive systems with respect to whether an extended airactivated drying mode to volatilize the solvent should be performed before curing. Thus, this study aimed to evaluate the DC of commercially available adhesive systems when photo-activated after extended air-activated or passive methods of solvent volatilization.…”
Section: Introductionmentioning
confidence: 99%
“…Acetone is used frequently as a solvent because it can efficiently remove water from surfaces 25,26,28) . By adding 10% acetone to water, the vapor-pressure increases by more than 300%, leading to volatilization of some of the surface water 29) . 대한치과보존학회지: Vol.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Dentre esses componentes, os solventes utilizados têm importância fundamental, pois auxiliam no deslocamento das moléculas de água, permitindo a maior penetração dos monômeros hidrofílicos. Por outro lado, características químicas desses solventes, como a volatilidade, acabam por requerer maiores cuidados durante a manipulação e o armazenamento dos frascos de adesivo (ABATE; RODRÍGUEZ; MACCHI, 2000;GIANNINI et al, 2008;KLEIN JR et al, 2008). Além da água, que pode ser utilizada como solvente inorgânico, os principais solventes orgânicos utilizados são acetona, etanol e uma associação de etanol e água (NUNES; SWIFT JR; PERDIGÃO, 2001).…”
Section: Introductionunclassified